Design and production of sintered β-tricalcium phosphate 3D scaffolds for bone tissue regeneration - Santos, Carlos Filipe Lopes (2018)
The characteristics of sintered β-tricalcium phosphate (β-TCP) scaffolds produced by 3D printing were studied by means of X-ray diffraction, Scanning Electron Microscopy, Fourier transform infrared spectroscopy, uniaxial compression tests and cytotoxicity tests, using human osteoblast cells. The results reported include details of the β-TCP scaffolds' porosity, density, phase stability, mechanical behavior and cytotoxic profile. Collectively, these properties are fundamental for the future application of these scaffolds as bone substitutes for individualized therapy.